Pemahaman Siswa Tentang Penerapan Protokol Kesehatan Selama Pembelajaran Tatap Muka - Armenia Diah Sari; Triani Rahmadewi (Institut Citra Internasional, 2023)
Coronavirus Disease 2019 (COVID 19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV-2). The ages range which has the risk of COVID-19 infections are school aged children and adolescents. Face-to-face learning at schools has to be held carefully so that the schools do not become new cluster of COVID-19 infection. Students’ knowledge and attitudes are very fundamental in health protocols implementation during face-to-face learning process. The study aims at describing students’ knowledge on and attitudes towards health protocols implementation during face-to-face learning at Muhammadiyah Mutihan Elementary School of Wates Yogyakarta. The study design was analytical descriptive with cross-sectional approach. The samples of the study were 85 students and were taken by using purposive sampling technique through knowledge and attitudes questionnaire. The result revealed that related to students’ knowledge on health protocols implementation, 58% of students was in good category and 42.2% of students was in poor category. Meanwhile, related to students’ attitudes the result found that 76.5% of students was in good category and 23.5% of students was in poor category. Schools should maintain students’ knowledge related to health protocols implementation at schools and always provides education for students in terms of health protocols implementation at schools during face-to-face learning.